Investigation of microplastics in the tilapia found in Lake Victoria, Kenya - Nicholson, Holly (2021)
Fish play an important role in food and nutritional security around the world. Their consumption offers unique nutritional and health benefits and is considered a key element in a healthy diet. Increased attention is given to fish as a crucial source of protein and other essential nutrients. With a growing global population, the demand for fish is increasing with this increased demand mainly being met from the increased output of aquaculture products, and not from wild sources. Approximately 200 million people in Africa derive high-quality and low-cost proteins from fish. The fisheries and aquaculture sectors in Africa are increasingly contributing to food and nutrition security, foreign exchange and employment. The aquaculture industry on the continent is growing faster than any other part of the world, with countries such as Kenya realising the potential of this industry to provide a sustainable source of affordable protein. The fishery industry faces many challenges, including climate change, and the pollution of aquatic ecosystems. One pollutant of key concern are microplastics, which are causing an environmental crisis by polluting our aquatic environments and threatening the health of fish and humans. The aims of this study were to assess microplastic prevalence in tilapia fish, both wild and farmed, sourced from Lake Victoria, Kenya. The study investigated the prevalence of the five main microplastic types, fragment, foam, film, fibre and bead, by fluorescent light microscopy in both fish muscle and gastrointestinal tract (GIT). In addition, we investigated the presence of a plastisphere and conducted preliminary analyses into the composition of this community, by scanning electron microscopy and polymerase chain reaction. This study found 48% of the tilapia muscle samples and 100% of the GIT samples analysed to be contaminated with microplastics. The study found variability in microplastic prevalence between the farmed and wild fish. The muscle of wild fish had a greater prevalence than farmed fish, while the GIT of farmed fish had a greater prevalence than wild fish. Bacterial DNA was isolated from these microplastics and diatoms were also identified, potentially forming part of the plastisphere. Key elements were also identified often associated with the plastics. This study highlights the potential increased risk from ingestion of microplastics through the consumption of farmed (and wild) tilapia sourced from parts of Lake Victoria close to urbanisations and the mouths of key rivers draining into the lake. Further work is needed to identify the specific bacterial species present on the plastisphere and compare these between wild and farmed fish and between locations. This collective knowledge will inform the industry on the importance of monitoring microplastics in the lake and the life it supports as well as highlighting the importance of location for the siting of cages for fish farming. Further research into the potential effects these bacteria and chemicals adsorbed to the plastics may be having on fish and human health is essential.